2005
DOI: 10.1021/es0509275
|View full text |Cite
|
Sign up to set email alerts
|

Push−Pull Tests to Quantify In Situ Degradation Rates at a Phytoremediation Site

Abstract: Nine push-pull tests (PPTs) were performed to determine in-situ aerobic respiration rates at a creosote-contaminated site and to assess the contribution of hybrid poplar trees to the remediation of polynuclear aromatic hydrocarbons (PAH) in groundwater. PPTs were conducted by injecting a solution containing dissolved oxygen and naphthalene (reactive tracers) with bromide (nonreactive tracer) into wells constructed in a shallow unconfined aquifer. The objective of this study was to determine seasonal variation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
(49 reference statements)
0
9
0
Order By: Relevance
“…Because of limited time to conduct the pilot test and the constraint to use the existing monitoring well network, the field pilot test consisted of single-well injection tests in three wells that ranged from 85 to 120 feet (25.9-36.6 m) in depth (Table S1). The single well injection tests were similar to single well "push-pull" tests that have been used often for costeffective pilot tests (Pitterle et al, 2005;Harrison et al, 2011) but incorporated passive sampling. Injection volumes were calculated using the well characteristics and known porosity (Table S1) to achieve desired amendment concentrations in a 1.5-m radius of influence from the well.…”
Section: Field Pilot Testmentioning
confidence: 99%
“…Because of limited time to conduct the pilot test and the constraint to use the existing monitoring well network, the field pilot test consisted of single-well injection tests in three wells that ranged from 85 to 120 feet (25.9-36.6 m) in depth (Table S1). The single well injection tests were similar to single well "push-pull" tests that have been used often for costeffective pilot tests (Pitterle et al, 2005;Harrison et al, 2011) but incorporated passive sampling. Injection volumes were calculated using the well characteristics and known porosity (Table S1) to achieve desired amendment concentrations in a 1.5-m radius of influence from the well.…”
Section: Field Pilot Testmentioning
confidence: 99%
“…To create the realizations, a vertical plane was passed through the DNAPL release point in the 3‐D domain and one or two 2‐D rectangular—40 cm high ( normalH) × 120 cm long ( normalL)—subsections were manually selected from each transect plane, representative of a range of spill and permeability metrics. The size of these 2‐D subsections was chosen consistent with the scale of the zone interrogated in a typical single well PPTT [e.g., Istok et al ., ; Pitterle et al ., ].…”
Section: Methodsmentioning
confidence: 99%
“…Naphthalene is the primary contaminant volatilized into pore air and dissolved into groundwater from the creosote, which is present as a dense nonaqueous phase liquid (DNAPL) in the surficial aquifer. Previous studies at the site demonstrated that naphthalene undergoes preferential remediation over the PAHs with three or more rings and enhanced biodegradation is occurring in areas impacted by poplar trees (1,2). Direct volatilization of naphthalene to the atmosphere was measured at the site and found to be enhanced by the presence of the phytoremediation system because the trees reduce the saturated thickness separating the submerged DNAPL and the water table and thus enhance vertical fluxes of contaminants (3).…”
Section: Introductionmentioning
confidence: 91%